2011
DOI: 10.1088/0953-4075/44/18/184014
|View full text |Cite
|
Sign up to set email alerts
|

The influence of electron screening on disorder-induced heating

Abstract: Ultracold plasmas are formed by ionizing laser-cooled gases. The spatial disorder in the initial plasma state gives rise to rapid ion heating called disorder-induced heating. The heating rate depends on the electron temperature because lower temperature electrons more effectively shield neighbouring ion charges from one another. We illustrate the effect of electron shielding on the ion thermalization rate in ultracold plasmas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
(33 reference statements)
1
27
0
Order By: Relevance
“…Previous studies have shown that electron screening can significantly reduce the ion temperature and slow the DIH time scale [10,12]. At first sight this appears to increase Γ.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown that electron screening can significantly reduce the ion temperature and slow the DIH time scale [10,12]. At first sight this appears to increase Γ.…”
mentioning
confidence: 95%
“…These plasmas are typically generated by photo-ionizing lasercooled gases [1] or gases in an ultrasonic jet [2]. They are diagnosed using three-body recombination [3][4][5][6][7][8], thermalization rates [9][10][11][12], electron evaporation or rf absorption [3,[13][14][15][16][17][18], charged particle imaging and detection [2,19], and optical fluorescence [12,20,21] and absorption [22][23][24]. Theoretical calculations and simulations [25][26][27][28][29][30][31][32] give great insights into the properties of these plasmas.…”
mentioning
confidence: 99%
“…When the electron screening length is comparable to the distance between particles, screening changes the ion dynamics Lyon and Bergeson, 2011). The ion-ion interaction can be modeled using a Yukawa potential (see Eq.…”
Section: Electron Shielding 1 γmentioning
confidence: 99%
“…It is also possible to create strongly coupled ultracold plasmas by ionizing atoms in a gas jet (Heilmann et al, 2012;Morrison et al, 2008;Sadeghi et al, 2014). These plasmas are diagnosed using three-body recombination (Bannasch and Pohl, 2011;Bergeson and Robicheaux, 2008;Fletcher et al, 2007;Killian et al, 2001;Pohl et al, 2008;Sadeghi et al, 2011), thermalization rates Castro et al, 2010;Lyon and Bergeson, 2011;McQuillen et al, 2011), electron evaporation or rf absorption (Bergeson and Spencer, 2003;Killian et al, 2001;Lu et al, 2011;Roberts et al, 2004;Rolston, 2010, 2012;Wilson et al, 2013), charged particle imaging and detection (Morrison et al, 2008;Zhang et al, 2008), and optical fluorescence (Cummings et al, 2005;Laha et al, 2007;Lyon and Bergeson, 2011) and absorption Killian, 2007;Simien et al, 2004). Theoretical calculations and simulations ( Jin-Xing et al, 2011;Kuzmin and O'Neil, 2002b;Mendonca and Shukla, 2011;Murillo, 2006;Park et al, 2010;Pohl et al, 2004;Robicheaux and Hanson, 2002;Shukla and Avinash, 2011) give great insights into the properties of these plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Many UCP experiments use an ion absorption imaging to deduce UCP parameters 17,18 . Such techniques use near resonant laser pulses to illuminate the UCP.…”
Section: Ion Doppler Profilesmentioning
confidence: 99%